2021
DOI: 10.1093/ntr/ntab108
|View full text |Cite
|
Sign up to set email alerts
|

Unburned Tobacco Cigarette Smoke Alters Rat Ultrastructural Lung Airways and DNA

Abstract: Introduction Recently, the Food and Drug Administration (FDA) authorized the marketing of IQOS Tobacco Heating System as a Modified Risk Tobacco Product (MRTP) based on an electronic heat-not-burn technology that purports to reduce the risk. Methods Sprague-Dawley rats were exposed in a whole-body mode to IQOS aerosol for 4 weeks. We performed the chemical characterization of IQOS mainstream and we studied the ultrastructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
(63 reference statements)
1
17
0
1
Order By: Relevance
“…A recent in vivo study demonstrated that irritating and carcinogenic compounds including aldehydes and polycyclic aromatic hydrocarbons are contained in the IQOS mainstream and indicates that IQOS causes grave lung damage and promotes factors that increase cancer risk [ 31 ]. Meanwhile, a recent review suggests that HTPs may be products with a reduced risk of chronic diseases, including respiratory and cardiovascular diseases and cancer, compared to traditional smoking, although exposure to IQOS has been reported to alter mitochondrial function, which may further exaggerate airway inflammation, airway remodeling and lung cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo study demonstrated that irritating and carcinogenic compounds including aldehydes and polycyclic aromatic hydrocarbons are contained in the IQOS mainstream and indicates that IQOS causes grave lung damage and promotes factors that increase cancer risk [ 31 ]. Meanwhile, a recent review suggests that HTPs may be products with a reduced risk of chronic diseases, including respiratory and cardiovascular diseases and cancer, compared to traditional smoking, although exposure to IQOS has been reported to alter mitochondrial function, which may further exaggerate airway inflammation, airway remodeling and lung cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, building on the industry’s earlier tactical co-option of harm reduction terminology,27 PMI is now attempting to redefine the concepts ‘smokefree’ (away from the complete absence of tobacco products) and ‘quitting’ (away from ending the use of tobacco and nicotine products). Its presentation of iqosas ‘smokefree’ may not be entirely accurate, due to the pyrolysis that occurs when the tobacco is heated 51 52. Similarly, PMI publishes estimates of ‘quitting’ based on the number of people who have ‘switched’ to iqos, even for a brief period, including dual users alongside cigarettes 16.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to note that emissions from earlier generation of HTPs (e.g., Eclipse) were classed as smoke by a study affiliated to the manufacturer 39 ( Table 1 ), and the emissions were also found to contain soot (black carbon). 40 In addition, Vivarelli et al 41 refers to IQOS aerosol as smoke containing carcinogenic compounds, including aldehydes and polycyclic aromatic hydrocarbons, that are sign of incomplete combustion and degradation of tobacco. This raises the question as to what extent IQOS emissions differ from those from these earlier HTPs so as not to be classed as smoke.…”
Section: To What Extent Can Iqos Be Considered Smoke Free?mentioning
confidence: 99%